Land-cover change in the department of Vichada, Colombia, from 1985 to 2017 - Vitar-Mendoza, Juan; Sandoval Parra, Karen X.; Ortiz Moreno, Martha L. (Revista de Investigación Agraria y Ambiental, 2021)
Contextualization: Colombia has experienced multiple land-cover changes derived from socio-economic policies that have reduced the high biodiversity of the country. Knowledge gap: In the Orinoquía region, the pressure to expand the agricultural frontier is increasing, without considering the importance of its natural resources. Purpose: This paper aimed to analyze the land-cover variations associated with agricultural practices, in the department of Vichada, with a special interest in vulnerable ecosystems, such as the Bita’s river basin, using Geographic Information System [GIS] analysis of historical images taken by a remote sensor from the United States Geological Service [USGS] Earth Explorer portal. Methodology:  Documental review and an analysis of satellite images from 1985 to 2017. Results and conclusions: The results showed that in Vichada, during a 32-year period, there was a transition from forest to cropland and pastures, in which 60% of the forest cover got lost. Moreover, areas of natural savannas were also replaced with pastures for livestock production. These land-cover changes were associated with government policies that fomented illegal occupation of land, monocultures, and non-native plantation forests. Bita’s river basin also lost a significant part of forest cover because of agribusiness development in the municipality of Puerto Carreño (Vichada). These land-cover changes have an impact on the ecological integrity of significant ecosystems and in their functionality in the region, that is why, conservation measures must be implemented.